2013
DOI: 10.1186/1471-2482-13-s2-s53
|View full text |Cite
|
Sign up to set email alerts
|

Role of conventional radiology and MRi defecography of pelvic floor hernias

Abstract: BackgroundPurpose of the study is to define the role of conventional radiology and MRI in the evaluation of pelvic floor hernias in female pelvic floor disorders.MethodsA MEDLINE and PubMed search was performed for journals before March 2013 with MeSH major terms 'MR Defecography' and 'pelvic floor hernias'.ResultsThe prevalence of pelvic floor hernias at conventional radiology was higher if compared with that at MRI. Concerning the hernia content, there were significantly more enteroceles and sigmoidoceles on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Some authors reported that to perform the examination using a state-of-the-art technique, which means dynamic MR imaging in supine position in closed magnet at rest, during squeezing, straining, and evacuation is probably more important than to consider the patient position [ 11 , 17 , 40 , 41 ]. In our previous experience, imaging the patients in supine position has been shown to be satisfactory in the evaluation of symptomatic pelvic floor weakness even if defects are best demonstrated when patients are sitting [ 42 , 43 ]. According to this, the results of the present study show that a statistically significant difference exists when the pelvic floor descent is evaluated in sitting versus supine position, and the MR study in supine position can underestimate the fixed descent (Figures 2 , 3 , and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that to perform the examination using a state-of-the-art technique, which means dynamic MR imaging in supine position in closed magnet at rest, during squeezing, straining, and evacuation is probably more important than to consider the patient position [ 11 , 17 , 40 , 41 ]. In our previous experience, imaging the patients in supine position has been shown to be satisfactory in the evaluation of symptomatic pelvic floor weakness even if defects are best demonstrated when patients are sitting [ 42 , 43 ]. According to this, the results of the present study show that a statistically significant difference exists when the pelvic floor descent is evaluated in sitting versus supine position, and the MR study in supine position can underestimate the fixed descent (Figures 2 , 3 , and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main limitations of our study were the small number of patients and the lack of postoperative anal ultrasound and anorectal manometry studies in patients with a more caudal peritoneal reflection, which could have provided not only topographic but also functional and anorectal anatomy information. Nevertheless, our findings provide further evidence that obesity and parity are anatomical risk factors for pelvic floor dysfunction that affect the location of the peritoneal reflection, concurrently with advanced age, estrogen deficiency, diabetes mellitus, pelvic radiotherapy, and orifice surgery, [24][25][26][27] although we found no significant correlations between the length of the peritoneal reflection and classical risk factors associated with the location of this important surgical anatomical landmark, such as female gender and patient height. Moreover, and importantly, we used a standardized protocol in living patients rather than in cadavers, unlike most anatomy studies.…”
Section: Discussionmentioning
confidence: 88%
“…Some studies compared conventional radiology and MRI defecography in order to determine the more suitable modality for pelvic floor hernias and other disorders, and it was determined that MRI defecography had a lower sensitivity in, for example, the detection of peritoneal sac herniations [ 250 ]. However, it was suggested that less invasive MRI defecography might be a strong candidate in the evaluation of the anatomy of the pelvic floor [ 256 ]. The best initial test for the diagnosis of constipation or obstructed defecation is transit time studies, followed by defecography.…”
Section: Imaging Of Gastrointestinal Diseasesmentioning
confidence: 99%